Analysis of Ability to Pay and Willingness to Pay in Trans Sulawesi Train Makassar - Parepare Route - Amaliah, Rizki; Widyastuti, Hera (EPI International Journal of Engineering, 2023)
The Trans Sulawesi train on the Makassar – Parepare route will traverse four significant stations with a planned length of ± 144 km and start operating in October 2022. Currently, it is not known the amount of travel fare applied to the Makassar - Parepare route. An analysis study of the ability to pay and willingness to pay for the Trans Sulawesi train for the Makassar - Parepare route aims to determine the value of the ability and willingness to pay for prospective service users to determine the Trans Sulawesi train rate. The data was collected by using interview surveys and distributing questionnaires through revealed preference and stated preference approaches. The ability to pay value was analyzed using the household budget method, and the willingness to pay value was analyzed based on the respondent's perception approach. Based on the results of the study obtained, the value of the ability to pay (ATP) of Rp. 144,279 and the value of willingness to pay (WTP) of Rp. 61,426.